Modified Cnn Based Heart Disease Detection Integrated With Iot (Journal of Pharmaceutical Negative Results, 2023)
The Internet of Things (IoT) and Artificial Intelligence have joined forces to change the conventional healthcare system into an intelligent model (AI). The deployment of critical technologies like the Internet of Things and artificial intelligence (AI) can help to improve medical care. In healthcare, IoT and AI have a variety of uses. The primary goal of the research is to develop an AI and IoT-based model for detecting heart illness. The concept uses a modified imperialist algorithm to diagnose heart problems (MICA). One of the most effective and efficient classification methods for medical data is the Modified Deep Convolutional Neural Network (MDCNN).It's been established to work in various of hospitalized patients. As a result, in the diagnosis of heart disease, the proposed modified imperialist competitive algorithm for feature selection (MICA) model is used to pick features. The simulation findings show that this suggestion enhances classification accuracy in experimental study using a benchmark dataset.